2018
DOI: 10.1667/rr14878.1
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of Head and Neck Radiation-Induced Mucositis and Distant Marrow Suppression in Fanca–/– and Fancg–/– Mice by Intraoral Administration of GS-Nitroxide (JP4-039)

Abstract: Squamous cell carcinomas of the head and neck are appearing with increased frequency in both marrow transplanted and non-transplanted Fanconi anemia (FA) patients. FA patients commonly display radiosensitivity of epithelial tissues, complicating effective radiotherapy. Fancd2 mice (C57BL/6J and 129/Sv background) demonstrate epithelial tissue sensitivity to single-fraction or fractionated irradiation to the head and neck and distant marrow suppression (abscopal effect), both ameliorated by intraoral administra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 42 publications
2
39
0
Order By: Relevance
“…Patients with FA demonstrate evolution of acute myeloid leukemia resulting from the malignant transformation of bone marrow of hematopoietic stem cells (9). The use of the long-term bone marrow culture system mouse model of FA has a great potential value for elucidation of the sequential mutation mechanisms involved in evolution of hematopoietic malignancies (5)(6)(7). Further studies should elucidate the sequential mutational changes in Fancd2 −/− long-term bone marrow cultures and derived hematopoietic cell lines which lead to final malignant transformation by a single HPV or other viral or microbial factors including other oncogenes.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with FA demonstrate evolution of acute myeloid leukemia resulting from the malignant transformation of bone marrow of hematopoietic stem cells (9). The use of the long-term bone marrow culture system mouse model of FA has a great potential value for elucidation of the sequential mutation mechanisms involved in evolution of hematopoietic malignancies (5)(6)(7). Further studies should elucidate the sequential mutational changes in Fancd2 −/− long-term bone marrow cultures and derived hematopoietic cell lines which lead to final malignant transformation by a single HPV or other viral or microbial factors including other oncogenes.…”
Section: Discussionmentioning
confidence: 99%
“…SOD1 G93A and control SOD1 transgenic mice containing 4 copies of normal human SOD1 gene were obtained from the Jackson Laboratories, Bar Harbor, Maine. SOD1 G93A -green fluorescent protein (GFP + ) mice were bred according to published methods used to breed SMAD family member 3 (Smad3) −/− Fanconi anemia group D2 (Fancd2) −/− mice (59). Mice were derived from breeding pairs of SOD1 G93A and control mice.…”
Section: Methodsmentioning
confidence: 99%
“…Mice were given no irradiation, 9 Gy, or 7.0 Gy TBI using a Shephard Mark I 137 Cs γ-ray source (J. L. Shepherd, San Fernando, CA, USA), according to published methods (59). Other mice received 9 Gy cranial spinal irradiation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, several groups are studying the use of radiation protector agents. Animal models using FANCD2 −/− (FVB/N) mice, FANCD2 −/− (C57BL/6) mice, and FANCA −/− and FANCG −/− mice showed that the intraoral administration of JP4‐039 (GS‐nitroxide) before each radiation treatment improves local normal tissue radiosensitivity and distant bone marrow suppression. These results support the need for clinical trials with this agent for future use in clinical RT for patients with FA.…”
Section: Treatment Of Oscc In Famentioning
confidence: 99%